TRANSMISSION OF A MULTIPLEXED EIGHT CHANNELS SUBCARRIER OPTICALLY INTENSITY MODULATED BASED ON MICROCONTROLLER (Journal of Engineering, 2009)
An optical fiber communication system for transmitting eight time division multiplexed analog signals each of bandwidth of 500 Hz was designed and implemented. The system utilizes the 8051 microcontroller as a parallel to serial converter in the transmitter side and parallel to serial converter in the receiver side inaddition to the control process of the multiplexer and demultiplexer in both sides and for serial transmission via its RS232. The transmitted signal is subcarrier intensity modulated using the Amplitude Shift Keying (ASK) modulation technique with a carrier of 20 MHz. A laser diode of the type HFCT-5205 at 1300 nm wavelength was used as an optical carrier generator with an emitted optical power of -10 dBm, and a HFCT-S205 InGaAs/InP PIN Photodiode with responsivity of 0.36 A/W at the receiver side. A single mode fiber of (42 km) length was used as a tranasmission channel. This system can be utilized in the TDM fiber telephone lines often operating at higher rates such as T3 (44.7 Mbps), T3C (91 Mbps) and above.